Laparoscopic cholecystectomy Personal experience - Morelli Brum, Raúl (Cirugía del Uruguay, 2002)
In the period from March 1991 to August 2001, 759 cholecystectomies were performed laparoscopic by the same surgeon. The ages ranged from 17 to 83 years with a mean of 45 years. There were 472 (62%) women and 287 (38%) mens. 731 (96.3%) cholecystopathies were treated lithiasic and 28 (3. 7%) alithiasic cholecystopathies. From the lithiasic 93 (13%) were in acute thrust. No selection of patients was made, except for the asymptomatic patient older than 65 years with lithiasis the only one that was not intervened.